Enterprise applications: taking the open source option seriously - Navón, Jaime (2006)
Free and Open Source Software (FOSS) is becoming more popular. Nevertheless most CIOs wouldn’t even consider this option for their enterprise information technology needs. We found that the three main concerns about FOSS have to do with legal issues, costs and support. We propose an initial framework to look at FOSS in a balanced, unbiased and systematic manner that can be used for evaluation of specific scenarios from very small companies to large ones.